Comparing Survival Following Hip Fracture Repair in VHA and Non-VHA Facilities. (March 2015) - Hutt, Evelyn; Radcliff, Tiffany A.; Henderson, William; Maciejewski, Matthew; Cowper-Ripley, Diane; Whitfield, Emily
Introduction: Although postsurgical outcomes are similar between Veterans Health Administration (VHA) and non-VHA hospitals for many procedures, no studies have compared 30-day and 1-year survival following hip fracture repair. Therefore, this study compared survival of veterans aged 65 years and older treated in VHA hospitals with a propensity-matched cohort of Medicare beneficiaries in non-VHA hospitals. Materials and Methods: Retrospective cohort study of 1894 hip fracture repair patients in VHA or non-VHA hospitals between 2003 and 2005. Current Procedural Terminology codes identified 3542 male patients aged> 65 years who had hip fracture repair between 2003 and 2005 in the Veterans Affairs' National Surgical Quality Improvement Program database. The Medicare comparison sample was drawn from 2003 to 2005 Medicare Part A inpatient hospital claims files. To create comparable VHA and Medicare cohorts, patients were propensity score matched on age, admission source (community vs. nursing home), repair type, comorbidity index, race, year, and region. Thirty-day and 1-year survival after surgery were compared between cohorts after further adjustment for selected comorbidities, year of surgery, and pre- and postsurgical length of hospital stay using logistic regression. Results: Odds of survival were significantly better in the Medicare than the VHA cohort at 30 days (1.68, 95% CI 1.15-2.44) and 1 year (1. 35, 95% CI 1.08-1.69). Conclusion: Medicare beneficiaries with hip fracture repair in non-VHA hospitals had better survival than veterans in VHA hospitals. Whether this is driven by unobserved patient characteristics or systematic care differences is unknown.